Blast resistance of auxetic and honeycomb sandwich panels: Comparisons and parametric designs. (1st January 2018) - Imbalzano, Gabriele; Linforth, Steven; Ngo, Tuan Duc; Lee, Peter Vee Sin; Tran, Phuong
Abstract: Equivalent sandwich panels composed of auxetic and conventional honeycomb cores and metal facets are analysed and compared for their resistance performances against impulsive loadings. The dynamic behaviours of these structures are numerically investigated, taking into account the rate-dependent effects. The Johnson-Cook model is employed to describe the dynamic responses of the composite sandwiches subjected to high strain-rate loadings. Analytical models are derived correlating unit cell geometrical parameters and crushing strengths of the representative panels at different impact velocities. Parametric studies are conducted to evaluate the performances of different sandwich panel designs under impulsive loadings. In particular, transmitted reaction forces and maximum stresses on the protected structure are quantified for various design parameters including the geometrical factors and the effective Poisson's ratios. A quarter of the panel is symmetrically modelled with shell elements and the CONWEP model is used to simulate the blast loading. Auxetic panels demonstrate interesting crushing behaviour, effectively adapting to the dynamic loading by progressively drawing material into the locally loaded zone to thereby enhance the impact resistance. Meanwhile, conventional honeycomb panels deform plastically without localised stiffness enhancement.